The effect of zig-zag and ladder drill training on sickle kick speed at the gsc pencak silat club - Azi Feriando; Lungit Wicaksono; Riyan Jaya Sumantri; Joan Siswoyo; Azi Feriando; Lungit Wicaksono; Riyan Jaya Sumantri; Joan Siswoyo (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2026)
The speed of the sickle kick is an important component of pencak silat that greatly affects the effectiveness of an attack and an athlete's performance. Proper physical exercises, such as zigzag running and ladder drills, are believed to increase agility and movement speed, ultimately contributing to increased kick speed. However, the effectiveness of these training methods still needs to be scientifically proven. This study aims to determine the effect of zigzag running and ladder drills on sickle kick speed and to compare the effectiveness of these training methods for pencak silat athletes. The study employed a quantitative experimental approach. The study population was participants in pencak silat training at Gisting Silat Club (GSC) in Tanggamus Regency. A sample of 30 people was taken using an ordinal pairing technique and divided into two treatment groups. The instrument used was a sickle kick speed test, and the data were analyzed using a t-test. The results showed that the zig-zag running exercise significantly increased the speed of the sickle kick (t-count: 8.411 > t-table: 2.145). Ladder drills also significantly increased speed (t count 4.063 > t table 2.145). However, there was no significant difference between the two training methods (t-count: 2.032 < t-table: 2.048).In conclusion, both types of exercise are effective in increasing the speed of the sickle kick; however, neither method is significantly superior. It is recommended that trainers use both methods in combination for optimal results.